Ontology support for translating negotiation primitives - Bravo, Maricela (2006)
In this paper we present an ontology solution to solve the problem of language heterogeneity among negotiating agents during the exchange of messages over Internet. Traditional negotiation systems have been implemented using different syntax and semantics. Our proposal offers a novel solution incorporating an ontology, which serves as a shared vocabulary of negotiation messages; and a translation module that is executed on the occurrence of a misunderstanding. We implemented a service oriented architecture for executing negotiations and conducted experiments incorporating different negotiation messages. The results of the tests show that the proposed solution improves the interoperability between heterogeneous negotiation agents.